Videogame Technology Re-Purposed: Towards Interdisciplinary Design Environments for Engineering and Architecture. (2015) - Moloney, Jules
Abstract: The author and associated researchers have in previous projects adapted videogame technology for design in the context of architectural design education. This paper reflects on this body of research: the original motivations and aspirations; what threads may be productively revisited; how contemporary shifts to parametric design and building information modelling may be incorporated; and considers how some aspects of game play, in particular competition, may seedInterdisciplinary Design environments for Engineering and Architecture (ID e EA).